Photosynthetic parameters of a sedge-grass marsh as a big-leaf: effect of plant species composition - Markéta Mejdová (Nature Portfolio, 2021)
Abstract The study estimates the parameters of the photosynthesis–irradiance relationship (PN/I) of a sedge-grass marsh (Czech Republic, Europe), represented as an active “green” surface—a hypothetical “big-leaf”. Photosynthetic parameters of the “big-leaf” are based on in situ measurements of the leaf PN/I curves of the dominant plant species. The non-rectangular hyperbola was selected as the best model for fitting the PN/I relationships. The plant species had different parameters of this relationship. The highest light-saturated rate of photosynthesis (Asat) was recorded for Glyceria maxima and Acorus calamus followed by Carex acuta and Phalaris arundinacea. The lowest Asat was recorded for Calamagrostis canescens. The parameters of the PN/I relationship were calculated also for different growth periods. The highest Asat was calculated for the spring period followed by the summer and autumn periods. The effect of the species composition of the local plant community on the photosynthetic parameters of the “big-leaf” was addressed by introducing both real (recorded) and hypothetical species compositions corresponding to “wet” and “dry” hydrological conditions. We can conclude that the species composition (or diversity) is essential for reaching a high Asat of the “big-leaf ”representing the sedge-grass marsh in different growth periods.